Pola Komunikasi Verbal Orang Tua Anak Berkebutuhan Khusus (Disabilitas Slow Learner) - Rubiani, Yen Yuan; Ahmad, Silmi Halimatusay'diah; Rizqillah, Muhamad; Nurhadi , Zikri Fachrul (Program Studi Ilmu Komunikasi UII, 2023)
Communication with children with special needs has different communication patterns; it is the basis that must be owned by parents who have children with special needs. The purpose of this study is to explain how parents with children with special needs often use verbal communication patterns as slow learners. The method used in this research is a qualitative method with a symbolic interaction theory approach through observation, interview, and literature data collection techniques. The results of this study indicate that parents of children with special needs (slow learners) have a structured verbal communication pattern and are the same as the communication patterns of parents of ordinary children. They use communication strategies tailored to the child's needs, repetition, understanding, and simplicity. This can be the basis for a support program for parents when communicating with slow learners.